Framework teórico e computacional para estruturas de concreto armado : implementação de modelos de armadura e aderência - Saulo Silvestre de Castro (2013)
With the advent of digital computers, together with accumulated knowledge after years of study on the behavior of simple and reinforced concrete, several numerical models have been developed. Among several developed models, the models based on the Finite Element Method have shown to be powerful tools for the analysis of reinforced, simple and prestressed concrete structures. In this context, the inclusion of the reinforcement in the analysis of reinforced concrete structures can be made using three different models: smeared reinforcement models, discrete reinforcement models, embedded reinforcement models. In the first two models, the phenomenon of bond-slip can be included, making them more realistic and, therefore, more popular. This dissertation presents the discrete reinforcement models, the embedded reinforcement models and link and contact element to include bond-slip. Those models were incorporated into INSANE (INteractive Structural ANalysis Environment), computer system for structural analysis developed at the Department of Structural Engineering of UFMG. Several problems were analyzed using the models included, aiming to validate the implementation made.